COMMERCIAL HERBAL ADMINISTRATION FOR PREVENTING Vibrio parahaemolyticus INFECTION IN VANNAMEI SHRIMP (Litopenaeus vannamei) - Putra, The Best Akbar Esa; Widanarni, Widanarni; Wahjuningrum, Dinamella; Yuhana, Munti (Agency for Marine and Fisheries Extension and Human Resources, 2024)
Vibrio parahaemolyticus is one of the pathogens in crustaceans that can cause mass death in vannamei shrimp farming. This study aimed to evaluate the effect of administering the commercial herbal supplement Phycurma Aquatic (PA) through feeding at different doses to prevent V. parahaemolyticus infection in vannamei shrimp. This study used a completely randomized design (CRD) consisting of five treatments and three replications, which are negative control group, positive control group, and PA at doses of 2.5, 5.0, and 7.5 mL kg-1 feed. Shrimps were reared for 30 days and fed five times a day. On the 31th day, shrimps were challenged with V. parahaemolyticus at a dose of 105 CFU mL-1, except for the negative control group. The results showed that the administration of 5.0 mL kg-1 of PA in the feed gave the best growth performance (P<0.05) compared to other treatments. The administration of 5.0 mL kg-1 PA in feed also enhanced shrimp health status and significantly increased the total hemocyte count, phagocytic activity, respiratory burst, and phenoloxidase. Furthermore, the administration of PA also increased antioxidant activity, reduced malondialdehyde levels, decreased V. parahaemolyticus population in the intestine, and reduced hepatopancreas tissue damage. Moreover, the survival rate of vannamei shrimp before and after the challenge test in the treatment group with a dose of 5.0 mL kg-1 of PA was significantly higher (P<0.05) compared to other treatments.